Candy Bee: innovating pollen into modern snacks for beekeepers in Kampung Madu Tourism Village - Agung Witjoro; Claresia Tsany Kusmayadi; Halimatus Sa'diyah; Cassandra Permata Nusa; Ilmi Dewi Astuti; Dinar Arsy Anggraini (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Kampung Madu Tourism Village in Bringin Village, Kediri, is renowned as a center for natural honey production. However, the lack of product diversification has limited the economic value for the local community. This community engagement program utilized bee pollen, a nutrient-rich byproduct of beekeeping, as the main ingredient for the innovative candy product, "Candy Bee." The Participatory Action Research (PAR) approach is applied as the implementation method, directly involving the community in production and marketing. The partners in this initiative are local beekeepers based in the Kampung Madu Tourism Village. Results showed high enthusiasm among participants in creating innovative products with increased market value. Through branding and entrepreneurship training, the program successfully enhanced beekeepers' skills and unlocked new economic potential. This diversification effort is expected to strengthen Kampung Madu as a leading ecotourism destination. The implementation of this program has implications for empowering local communities to engage in value-added production, fostering innovation-based entrepreneurship, and inspiring the development of creative agroindustry models in other rural tourism areas.